Cholesterol granuloma of the maxillary sinus - Almada,Cinthya Bessa da Motta (2008)
Cholesterol granuloma (CG) is a foreign body reaction to the deposition of cholesterol crystals, usually found in association to chronic middle ear diseases, being highly uncommon in the paranasal sinuses. This article reports a case of CG in the maxillary sinus of a 22-year-old man, manifesting as a swelling on the right maxilla associated with pain and nasal obstruction. Computed tomography (CT) imaging showed complete opacification of the right maxillary sinus with cortical bone expansion and destruction. Incisional biopsy showed a solid mass filling the sinus and histological examination showed foreign body reaction to cholesterol crystals. The microscopic findings associated to tooth vitality, CT images and absence of a cavity during the surgical procedure were compatible with the diagnosis of CG of the maxillary sinus. Complete surgical excision of the mass under general anesthesia was suggested, but the patient did not return to conclude the treatment. CG must be included in differential diagnosis of diseases that cause opacification on the paranasal sinuses, especially sinusitis, and cystic and tumoral lesions.